Aplikasi Reminder Pengobatan Pasien Penyakit Diabetes Berbasis SMS Gateway Di Puskesmas Kampung Bali Kota Bengkulu - Utama, Andiko Halim; Siswanto, Siswanto; Rohmawan, Eko Prasetiyo (LPPM UNIKA Santo Thomas Medan, 2021)
So far, not all DM patients know the schedule of treatment at the Kampung Bali Health Center, Bengkulu City, because the information about the patient's treatment is not / lacking. In addition, the Kampung Bali Bengkulu Community Health Center does not yet have an application that can manage diabetes patient care schedules and there is also no interactive forum for the public to find out information about diabetes patient care at the Kampung Bali Bengkulu Community Health Center. so that the health center has difficulty in providing information to diabetes patients. diabetes about the next treatment schedule. Application Reminder Treatment for Diabetes Patients at Kampung Bali Health Center, Bengkulu City is an SMS Gateway-based application that can be used to process data about Medications, Patients, Medicines, Treatment Schedules, and can also send SMS to patients individually, and patients can also get information . This diabetic patient medication reminder application features SMS Gateway, SMS Reminder. Application Reminder Treatment for Diabetes Patients at the Kampung Bali Health Center, Bengkulu City, was created using the PHP programming language, MySQL Database, and Gammu. The tool used to receive and based on tests that have been carried out, the Reminder Application for Diabetes Treatment Patients at the Kampung Bali Community Health Center, Bengkulu City can do an SMS Reminder / Schedule (which sends an SMS notification / reminder about the immunization schedule 1 day before the due date)